Coastal Community Empowerment Based on Local Wisdom and Technological Innovation for Climate Change Adaptation, Erosion Control, and Sustainable Ecotourism Development - Ridwan, R. Ery; Julianto, Muhammad Aditya; Marpaung, Putri Nauli; Utami, Annisa Ratri; Ismail, Taufik; Wijayanti, Sintia Wahyu; Subroto, Sri Tanjung; Farizan F, Dike; Setiawan, Rizal Justian (Sustainable Marine Structures, 2025)
This study evaluates the effectiveness of integrating local wisdom with the use of Alat Pemecah, Peredam Ombak, dan Sedimen Traps (APPOSTRAPS) or Breakers, Wave Dampers, and Sediment Traps in empowering coastal communities in Karawang, Indonesia, as a strategic response to climate change, coastal erosion, and sustainable ecotourism development. The research aims to assess the combined impact of APPOSTRAPS technology and the Jaga Alam Melalui Pemberdayaan Masyarakat Pesisir (JAM PASIR) or Protecting Nature Through Coastal Community Empowerment program in reducing coastal abrasion, restoring mangrove ecosystems, and fostering sustainable livelihoods. A mixed methods approach was applied, combining quantitative analysis of coastline changes using Geographic Information System (GIS) with Landsat and Sentinel-2 imagery (2022–2024), field surveys using differential GPS (±2 m accuracy), and qualitative methods including 150 interviews, 18 months of participant observation, and community documentation. Results show a coastline extension of about 400 m (±15 m), increased ecotourism revenue from IDR 11.25 million per month in 2019 to IDR 90 million in 2024, women’s participation rising from 12% to 68%, and livelihood diversification reaching 110% of the target with 98 families involved. APPOSTRAPS, a patented breakwater and sediment trap made from repurposed tires, combined with the JAM PASIR program covering mangrove-based ecotourism, MSMEs for fishermen’s wives, waste management, and the Masyarakat Sadar Lingkungan and Bencana (MASDARLINA) or Environmentally and Disaster Aware Society system, effectively mitigates erosion and supports economic growth. The study concludes that integrating indigenous knowledge and technology strengthens community resilience and provides a replicable model for sustainable coastal adaptation. ER